The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1101/gad.8.7.796
|View full text |Cite
|
Sign up to set email alerts
|

UME6 is a key regulator of nitrogen repression and meiotic development.

Abstract: This report describes the identification, cloning, and molecular analysis of UME6 (CAR80/CARGRI), a key transcriptional regulator of early meiotic gene expression. Loss of UME6 function results in the accumulation of fully derepressed levels (70-to 100-fold increase above basal level) of early meiotic transcripts during vegetative growth. In contrast, mutations in five previously identified UME loci (UME1 to UME5), result in low to moderate derepression (2-to 10-fold increase) of early meiotic genes. The behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
272
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(286 citation statements)
references
References 75 publications
(77 reference statements)
13
272
1
Order By: Relevance
“…To identify candidate transcriptional regulators of ATG8, we analyzed its promoter region and identified an upstream regulatory sequence, URS1, which is a consensus binding site for the transcription factor Ume6 (Fig. 1A), which was previously identified during a whole-genome microarray analysis (9)(10)(11). The URS1 consensus site consists of two invariant GGC repeats, which tend to be immediately preceded by a C and several T nucleotides and followed by a T and two A nucleotides, although some variability exists in these positions (9).…”
Section: Resultsmentioning
confidence: 99%
“…To identify candidate transcriptional regulators of ATG8, we analyzed its promoter region and identified an upstream regulatory sequence, URS1, which is a consensus binding site for the transcription factor Ume6 (Fig. 1A), which was previously identified during a whole-genome microarray analysis (9)(10)(11). The URS1 consensus site consists of two invariant GGC repeats, which tend to be immediately preceded by a C and several T nucleotides and followed by a T and two A nucleotides, although some variability exists in these positions (9).…”
Section: Resultsmentioning
confidence: 99%
“…Ume6-regulated genes were expected to fall into two major classes: (i) direct target genes, whose promoters are bound by Ume6, and (ii) indirect targets showing altered expression as a result of downstream effects caused by loss of Ume6. To identify the subset of genes that are most likely direct targets of Ume6, the promoters of differentially expressed genes (Ϫ600 to ϩ200 with respect to the ATG start codon) were screened for the presence of the core hexamer URS1 A sequence (5Ј-GGCGGC-3Ј or its reverse complement) bound by Ume6 in vivo and in vitro (2,17).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies in our lab and others showed that Ume6 is a major regulator of early meiotic expression (2,10,22,35). Indeed, the present analysis shows that a significant fraction of Ume6 activity is devoted to meiotic functions, because more than half of the known direct Ume6 targets play important roles , metabolism (16%), cell growth͞division͞DNA synthesis (12%), intracellular transport (9.5%), cell rescue͞defense͞aging (8.1%), transcription (8.1%), cellular biogenesis (6.8%), protein destination (6.8%), protein synthesis (6.8%), transport facilitation (4%), ionic homeostasis (2.7%) (40).…”
Section: Ume6 May Play a Broader Role In Meiosis And Spore Formation mentioning
confidence: 99%
See 2 more Smart Citations